Nanocrystal-Embedded-Insulator (NEI) Ferroelectric FETs for Negative Capacitance Device and Non-Volatile Memory Applications - Peng, Yue (Nanoscale Res Lett, 2019)
We report a novel nanocrystal-embedded-insulator (NEI) ferroelectric field-effect transistor (FeFET) with very thin unified-ferroelectric/dielectric (FE/DE) insulating layer, which is promising for low-voltage logic and non-volatile memory (NVM) applications. The ferroelectric nature of the NEI layers comprising orthorhombic ZrO(2) nanocrystals embedded in amorphous Al(2)O(3) is proved by polarization voltage measurements, piezoresponse force microscopy, and electrical measurements. The temperature dependent performance and endurance behavior of a NEI negative capacitance FET (NCFET) are investigated. A FeFET with 3.6 nm thick FE/DE achieves a memory window larger than 1 V, paving a pathway for ultimate scaling of FE thickness to enable three-dimensional FeFETs with very small fin pitch.